Multivariable Analysis of Risk Factors Affecting Dislocation After Bipolar Hemiarthroplasty in Patients with Femoral Neck Fracture - Yang Y; Fu G; Li Q; Zhang R; Liao W; Ma Y; Zheng Q (Dove Medical Press, 2022)
Yuhui Yang,1,* Guangtao Fu,1,* Qingtian Li,1,* Ruiying Zhang,1 Weihong Liao,1,2 Yuanchen Ma,1 Qiujian Zheng1,2 1Department of Orthopedics, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 2The Second School of Clinical Medicine, Southern Medical University, Guangzhou, 510515, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuanchen Ma; Qiujian Zheng, Email mayuanchen@gdph.org.cn; zhengqiujian@gdph.org.cnObjective: This study aimed to investigate the risk factors associated with dislocation and dissociation following bipolar hemiarthroplasty (HA) for the treatment of patients with femoral neck fractures.Methods: We retrospectively reviewed 462 patients (479 hips) treated with bipolar HA from January 2010 to January 2020. All patients received posterolateral approaches and a minimum follow-up of at least 2 years regularly. A case-control study was performed to analyze the risk factors of dislocation regarding patient demographics, coexisting diseases, surgical and morphologic features. Multivariable logistic regression analysis for independent risk factors affecting dislocation and dissociation was also performed.Results: The dislocation rate was 5.01%, and the mean time from HA to the first incident of dislocation was 38.75 days. Patient-related factors, including operation side, prosthesis type, and neuromuscular disease, did not differ significantly. Regarding the morphological factors, a significant difference was observed in center-edge (CE) angle, abduction angle, acetabular depth, depth/width ratio, rotation center (RC) to greater trochanter tip (GTT) vertical distance, RC to GTT vertical distance difference, RC to GTT horizontal distance, RC to GTT horizontal distance difference, offset difference, and offset discrepancy. Further, decreased CE angle, increased abduction angle, decreased RC to GTT vertical distance, decreased offset difference and increased offset discrepancy were determined to be independent risk factors of dislocation. The proportion of patients experiencing dissociation was 1.04%. All the implanted femoral heads were smaller than 43 mm, which was determined to be the risk factor of dissociation.Conclusion: Decreased CE angle, RC to GTT vertical distance, offset difference, and increased abduction angle, offset discrepancy were determined to be independent risk factors of HA dislocation. Once dislocation risk was detected by simulated templating, THA or changing surgical approach should be considered to avoid evitable perioperative complications.Keywords: bipolar hemiarthroplasty, dislocation, morphological evaluation, greater trochanter tip, offset